EFFECT OF ADDING NATURAL AGAINST SYNTHETIC ANTIOXIDANTS ON OVINE OOCYTE MATURATION, MALONDIALDEHYDE LEVELS, AND IN VITRO FERTILIZATION - A. F. Majeed; T. R. Mohammed; A. M. Ahmed (مجلة الأنبار للعلوم الزراعية)
A total of 608 ewe ovary samples were obtained from the abattoir and transported in a cool box containing normal saline. Oocytes (n=1368) were collected via aspiration and divided into eight treatment groups: T1 comprised Minimum Essential Media (MEM) + µmol 50 Capparis spinosa extract (CSE); T2 comprised MEM + 100 µmol Silymarin Extract (SE); T3 the MEM + 5 µmol Q10; C1 the MEM + control; T4 the Dulbecco's Modified Eagle Medium (DMEM) + 50 µmol CSE; T5 the DMEM + 100 µmol SE; T6 the DMEM + 5 µmol Q10; and C2 the MEM + Control. Increases were recorded for T1 and T5, the treatment with Silymarin extract (T2) and (T6) in all stages of embryonic development in vitro cleavage. There was a significant decrease (P<0.01) in MDA levels for the CSE and SE treatments in the same media as compared to the Q10 and control. In conclusion, treatment with CSE and SE improves the cleavage stage and development of morula and blastocysts though there was a decrease in malondialdehyde levels in the cultural media